2022
DOI: 10.3758/s13428-022-01998-y
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for the adaptive assessment of procedural knowledge and skills

Abstract: Procedural knowledge space theory (PKST) was recently proposed by Stefanutti (British Journal of Mathematical and Statistical Psychology, 72(2) 185–218, 2019) for the assessment of human problem-solving skills. In PKST, the problem space formally represents how a family of problems can be solved and the knowledge space represents the skills required for solving those problems. The Markov solution process model (MSPM) by Stefanutti et al. (Journal of Mathematical Psychology, 103, 102552, 2021) provides a probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A similar algorithm was proposed by [98] in the PKST framework. The main difference between the KST-based and the PKST-based algorithms is that the latter updates the likelihood on the basis of the whole observed solution process instead of using only the correct/wrong answer.…”
Section: Knowledge Space Theory Procedural Knowledge Space Theory And...mentioning
confidence: 99%
See 4 more Smart Citations
“…A similar algorithm was proposed by [98] in the PKST framework. The main difference between the KST-based and the PKST-based algorithms is that the latter updates the likelihood on the basis of the whole observed solution process instead of using only the correct/wrong answer.…”
Section: Knowledge Space Theory Procedural Knowledge Space Theory And...mentioning
confidence: 99%
“…The main difference between the KST-based and the PKST-based algorithms is that the latter updates the likelihood on the basis of the whole observed solution process instead of using only the correct/wrong answer. In [98], it was shown that the PKST-based algorithm outperforms the KST-based algorithm in terms of efficiency and accuracy since the former one employs more information from the observed data than the latter one.…”
Section: Knowledge Space Theory Procedural Knowledge Space Theory And...mentioning
confidence: 99%
See 3 more Smart Citations